Evaluation of Bioactivities of Gouania tiliaefolia Lam., an Indigenous Traditional Medicinal Plant of Bangladesh - Ahmed, Tufael; Khan, Rifat; Tabassum, Nafisa; Aktar, Fahima; Islam, Mohammad Kaisarul (Bangladesh Pharmaceutical Journal, 2019)
The crude methanol extract of Gouania tiliaefolia Lam. was partitioned by the modified Kupchan method and the fractions were evaluated for total phenolic content, antioxidant, cytotoxic, thrombolytic, hypotonic and heat-induced membrane stabilizing activities. The petroleum ether soluble fraction (PESF) and methanol extract (ME) showed the highest phenolic content of 78.30 ±1.60 mg and 70.37 ± 0.84 mg, respectively, which were expressed in gallic acid equivalent (GAE). Similar trends were observed in case of anti-oxidant and cytotoxic activities, where the PESF possessed the highest free radical scavenging activity and brine shrimp lethality (IC50 = 2.88 ± 0.02 μg/ml, LC50 = 2.59 ± 0.14 μg/ml), followed by ME (IC50 = 4.79 ± 0.17 μg/ml, LC50 = 3.38 ± 0.08 μg/ml) and CSF (IC50 = 37.51 ± 0.96 μg/ml, LC50 = 73.55 ± 0.26 μg/ml). In case of assays for thrombolytic and membrane stabilizing activities, all extractives showed insignificant results compared to the respective standards. The crude methanol extract of G. tiliaefolia was used to examine the in-vivo analgesic (central and peripheral), antidiarrheal and antidiabetic activities in Swiss albino mice. In case of castor oil induced diarrhea, the ME gave better reduction of diarrhea by 71.43% (at 400 mg/kg-body weight) compared to loperamide (64.29%). Antidiabetic activity was evaluated by oral glucose tolerance test and the ME showed 71.42% and 75.39% reduction of blood glucose at doses 200 and 400 mg/kg-body weight, respectively when compared with the standard glibenclamide that reduced blood glucose by 66.17%. The central- and peripheral-analgesic activity was evaluated by the tail-flick test and acetic acid induced writhing test, respectively. In both the cases, ME demonstrated dose-dependent analgesic activity compared to the standards. Bangladesh Pharmaceutical Journal 22(2): 200-207, 2019